Análisis socioeconómico del sector artesanal de los ex armeros asociados del barrio Tambán, cantón Chimbo, provincia Bolívar, año 2016 - Yuqui Colcha, Adriana Nathaly (2017)
The purpose of this paper is to analyze the socio-economic situation of the former armenians of Canton San Jose de Chimbo. In the San José de Chimbo Canton of the Bolivar Province, in 2010 there were 50 artisan workshops that were dedicated to the manufacture and commercialization of firearms of the country. Due to the increase of citizen insecurity, the National Government, through the decree "Presidential Commitment No. 17733" related to "Definitive prohibition of the manufacture and commercialization of artisanal firearms"; With which a market developed over centuries was closed. This activity allowed the economy of the Canton to remain stable as it provided employment to more than 50 families, including workers, hardware stores, cabinet makers (wooden handles for revolvers, boxes for shotguns and rifles), shops in the neighborhood, Etc. ie the Canton in general was affected by this presidential commitment. At present, no diagnosis has been made of the socioeconomic situation of the former artisanal arsenal after the issuance and implementation of this governmental provision, which serves as an instrument to propose a Development Plan aimed at improving their quality of life. The methodology that was used in the present investigation was through the Deductive and Inductive method; The types of research are: Field, and Descriptive, the universe to which the investigation was carried out correspond to 50 ex-armer heads of the workshops that had their respective permissions for the elaboration and commercialization of the weapons, granted by Captain Enrique Gómez, Chief of Arms Control in this Canton, giving us the economic situation before and after Government Prohibition. In order to achieve the results that statistically support the research work for its formulation and interpretation, it was developed as follows: Informative Data, Topic, Background or State of the Art, Justification, general and three specific objectives that help us to achieve the objective General, Theoretical Framework that allows us to know the reasons why the State took this decision to definitively close these workshops, idea to defend, the methodology, types of research, techniques and tools to obtain data, universe.